De (con)formar a formar com : o currículo vivido no curso de ambientação institucional do IFES - Robers, Danusa Simon (2013)
This research aimed at immersing in the quotidian routine of the Curso de Ambientação Institucional – CAI of Instituto Federal de Educação do Espírito Santo – Ifes, to discuss the knowledge-doing networks which are woven by the subjects who accomplish the course curriculum, that is, everyone who is, in a direct or indirect way, involved in creating and sharing quotidian networks of such curricula. Fostered, through researching on a daily basis, to weave networks of conversations with students, managers and teachers, having Alves, Azevedo, Carvalho, Certeau, Ferraço, Foucault, Ginzburg, Maturana and Perez as main theoretical intercessors with whom I engage a dialog throughout the research. Try to discuss a part of what happens on the environment of the course modules, in an attempt to translate those conversations-researches, showing the need of discussing: which feelings and/or processes of professional training that promote the production of a “beautiful life” are powered with the curriculum accomplished in the Curso de Ambientação Institucional at Ifes? I have worked with narratives, images, documents, songs and poetry throughout this dissertation, to try to translate moments, life experiences, meetings and involvements that took place throughout the research, presenting possibilities of reinventing the production of a beautiful life. The image-narratives of participants of the Curso de Ambientação Institucional aim at not separating our theoreticalmethodological-epistemological discussions of the data produced with the research.